The Effect Of Education Using Leaflet Media About Exclusive Breastfeeding On Knowledge In Third Trimester Pregnant Women At Tri Karya Mulya Health Center, Mesuji District - Betaria Dewanti; Yunita Anggriani; Inggit Primadevi; Wulan Dari (Sean Institute, 2024)
Pregnant women should prepare themselves to provide exclusive breastfeeding, due to the still relatively low breastfeeding achievement. Exclusive breastfeeding coverage in Mesuji District in 2022 was 67.17%, at Tri Karya Mulya Health Center with a target of 80% in 2022 was 45.57%. Efforts to increase breastfeeding achievement by providing education to pregnant women thus increasing knowledge. Educational media can use leaflets because they can be stored for a long time, targets can adjust and learn independently, users can view the contents during leisure time, wider target reach. The research objective was to determine the effect of education using leaflet media about exclusive breastfeeding on knowledge in pregnant women TM III at Tri Karya Mulya Health Center, Mesuji District in 2024. Quantitative research type with pre-experimental design with one group pretest-posttest. Population was all pregnant women TM III with a sample of 40 respondents taken by purposive sampling technique. The research was conducted at Tri Karya Mulya Health Center, Mesuji District in August 2024. Data collection used questionnaire sheets. Analysis was univariate and bivariate (Wilcoxon test). It was found that knowledge of pregnant women TM III before being given education using leaflet media was 60.6 and after was 89.3. There is an effect of education using leaflet media about exclusive breastfeeding on knowledge in pregnant women TM III (p-value = 0.000). Suggestions to health center staff and cadres to optimize the use of leaflet media in promoting exclusive breastfeeding to pregnant and breastfeeding mothers, pregnant women can seek information related to breastfeeding from health workers or the internet.